Aileron reversal and divergence of swept wings with special consideration of the relevant aerodynamic and elastic characteristics - Radok, J. R. M. (College of Aeronautics, Cranfield, 1952)
Using oblique coordinates, the static problems of Aero-elasticity for swept wings are reduced to the solution of integral – or matrix equations, which may be solved by iteration. The present treatment also indicates the suitability of integral equations for fundamental aero-elastic investigations. Continues …